41.0k views
2 votes
How do I do 2(x+1)-3x=14

2 Answers

0 votes

Answer:

it will be x= -12

Step-by-step explanation:

Distribute 2 to (x+1)

2x-3x+2=14

-1x+2=14

-2 -2

-1x=12

Divide -1x by -1 and 12 by -1

then x=12

User Steven Surowiec
by
6.1k points
3 votes

Answer:

x = -12

Explanation:

2(x+1)-3x=14 (expand parenthesis i.e PEDMAS rule)

2x + 2 - 3x = 14 (bring all x terms to one side and numbers to the other; subtract 2 from both sides)

2x - 3x = 14 - 2 (evaluate each side)

-x = 12 (multiply both sides by -1)

x = -12

User Jessieloo
by
6.0k points